Risk Analysis of Chemical Storage Room in Higher Education Laboratory - Adnan Malaha (Westscience Press, 2023)
Universities that have testing/experimental laboratories use chemicals and biology to support student competence and support the implementation of lecturer research which is one of the places that has a high enough risk of danger. Laboratory management such as chemical storage rooms should be managed based on the basic elements of laboratory management, namely planning, arrangement, administration, maintenance, security and supervision. so as to avoid the danger of poisoning, corrosive, skin irritation, fire, explosion which can pose a bad risk to health and the work environment. The aim of this research is to know the risks of chemical storage rooms with data collection techniques in the form of interviews, observation, and documentation which are analyzed using the Miles and Liberman model. The results showed the dangers of chemical storage rooms in the form of exposure to organic solvents, exposure to acidic liquids, irritants which are at risk of dizziness, nausea, shortness of breath, irritation, material damage and fire. With the potential coming from a lack of user knowledge, the absence of SOPs and MSDS and a lack of discipline in implementing PPE.